The Pindang Fish Quality is Based on Physical, Chemical, and Biological Parameters - Eni Setyowati; Haslinda Yasti Agustin (Postgraduate, University of Mataram, 2022)
Processing of fish products is mostly done by refining. However, spinning also has drawbacks, namely low durability and ease to rot. The purpose of the research was to test the quality of pindang fish physically, chemically, and biologically in the city of Tulungagung. The research method used is descriptive qualitative by testing the quality of pindang fish physically, chemically, and biologically. The results showed that physically pindang fish samples A and B were suitable for consumption with a value of more than 7. Chemical tests showed that samples A and B were safe for consumption when viewed from the content of salt, formalin, lead (Pb), tin (Sn), chromium (Cr), and mercury (Hg) which are all below the SNI standard. However, it should be noted that the content of water, cadmium (Cd), and arsenic (As) exceeds SNI. Biological tests showed the content of Escherichia coli, Salmonella spp. Staphylococcus aureus and Vibrio cholerae are all under the SNI, but there is one indicator, namely the Total Plate Number (ALT) which exceeds the SNI standard. Pindang fish found in the city of Tulungagung is suitable for consumption based on the results of physical, chemical, and biological tests.